The Handling of Armed Criminal Groups in Papua: Ended with Secession? - Rinasti, Avi Lupi; Alfarizi, Mohammad Hanaan; Noveliani, Regita Ryan; Farhansyah, Bagaskara Yonar; Astutik, Zulfiani Ayu (Universitas Muhammadiyah Yogyakarta, 2022)
The Papuan Armed Criminal Group (KKB) has been a hereditary problem for the Indonesian government. Their demand to secede from the Republic of Indonesia was the main reason why this group was formed. Because the Government has not responded to the demands of the KKB, it led this group to carry out acts of terror against the society in Papua. One of the cases that have recently attracted media attention is the KKB’s attack that killed several workers in Beoga, Puncak district, Papua. The study aims to analyze and evaluate the settlement of terrorism cases carried out by KKB. This normative legal research relied on secondary data. The results of the study indicate that in international law, the context of referendum exists only in the context of decolonization and non-self-governing territory. The government's move by considering the KKB as a separatist terrorist group and not accepting KKB's demands for a referendum or mediation is one of the right steps. Acts of terrorism cannot be tolerated even though they are related to human rights because it is regulated in legislation